Pemanfaatan Kecerdasan Buatan dalam Meningkatkan Higienitas Pangan - Felix King Lie; Eric Eric; Jessy Jessy; Jocelyn Jocelyn; Viona Angelina Herwanto (Journal of Information System and Technology (JOINT), 2023)
Food hygiene is one of the important factors in maintaining health, however food hygiene has not fully been implemented in the community. Therefore, Artificial Intelligence technology is presented in Society 5.0 to improve food safety and quality. This study aims to analyze opportunities for utilization of AI technology in the food sector. In conducting research ranging from problem identification, standard search, data collection, data analysis, to conclusions and suggestions. The results of the study obtained the magnitude of opportunities to utilize AI technology in the food sector. AI technology can improve the safety of food hygiene and facilitate monitoring of environmental hygiene, workers, or food itself.